Microgrid Development Using a Grid Tie Inverter - Santoso, Hartono Budi; Budiyanto, Budiyanto (UI Scholars Hub, 2013)
The use of renewable energy sources (RES), especially photovoltaic (PV), to meet the demand of electrical energy has been getting a great deal of attention as an alternative solution to electrical energy deficit problems. RES are being applied in power systems in a variety of configurations including microgrid systems. One of the characteristics of a microgrid is capability to supplying power to grid when there is an excess power to supply local load. This research examines the chances of saving power consumption from grid using power converters grid tie inverter (GTI) in a microgrid configuration. The test is done by using a zero load and power distribution methods. Test results show grid tie GTI capable of supplying electrical power to grid up to 98% of the input power converter. In the microgrid configuration power usage from grid can be reduced up to 91%, which should be supplied from the grid to load.